2008
DOI: 10.1038/oby.2008.277
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity and Eating Behaviors in Patients Under Second Generation Antipsychotics

Abstract: Background: Second generation antipsychotics (SGA) induce substantial weight gain but the mechanisms responsible for this phenomenon remain speculative. Objective: To explore eating behaviors among SGA-treated patients and compare them with nonschizophrenic healthy sedentary individuals (controls). Methods and Procedures: Appetite sensations were recorded before and after a standardized breakfast using visual analog scales. Three hours after breakfast, a buffet-type meal was offered to participants to document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 40 publications
(45 reference statements)
3
81
0
Order By: Relevance
“…A similar effect has been reported in humans. Patients on second-generation antipsychotics were found to be more responsive to external cues for eating and they felt less satiated after a meal than patients who were not on second-generation antipsychotics [34]. In this meta-analysis, only four out of the 13 studies put patients on a controlled diet, thus dietary differences between patient and controls groups should be taken into consideration [17,26,27,35].…”
Section: Discussionmentioning
confidence: 99%
“…A similar effect has been reported in humans. Patients on second-generation antipsychotics were found to be more responsive to external cues for eating and they felt less satiated after a meal than patients who were not on second-generation antipsychotics [34]. In this meta-analysis, only four out of the 13 studies put patients on a controlled diet, thus dietary differences between patient and controls groups should be taken into consideration [17,26,27,35].…”
Section: Discussionmentioning
confidence: 99%
“…38 Eating behaviour in patients treated with atypical APDs (clozapine, olanzapine, risperidone, quetiapine or ziprasidone) were also compared with health controls by recording appetite sensation before and after a standardized breakfast using visual analogy scales, and found that: (1) atypical APD-treated patients showed greater adiposity and a higher degree of hunger following the standardized breakfast; and (2) patients had significantly higher cognitive dietary restraint, disinhibition, and susceptibility to hunger than controls. 33 The patients treated with atypical APDs were also more reactive to external eating cues. 34 Furthermore, a recent study reported that, consistent with the significant increase of body weight, food consumption and disinhibited eating, one week treatment with olanzapine enhanced both the anticipatory and consummatory reward response to food rewards in the brain reward circuitry, including the inferior frontal cortex, striatum and anterior cingulate cortex, but decreased activation in the brain region (the lateral orbital frontal cortex) thought to inhibit feeding behaviour.…”
Section: The Effects Of Anti-psychotic Medication On Appetite/food Inmentioning
confidence: 99%
“…[32][33][34] On the other hand, there is less understanding of to what extent changes of resting metabolism rate and activity/sedation affect weight gain associated with APD medication, although current evidence suggests that they may play an important role in the development of APD-induced weight gain. 19,35,36 Altered eating behaviours have been reported in a number of clinical studies with treatment involving various APDs.…”
Section: The Effects Of Anti-psychotic Medication On Appetite/food Inmentioning
confidence: 99%
“…However, several clinical studies suggest that altered eating behavior is an important contributing factor: patients treated with atypical antipsychotics such as OLA frequently report an increase in appetite, appear more susceptible to hunger and experience ingested food as less satiating. [7][8][9][10] The regulation of appetite and eating behavior is determined by a complex interaction of different systems. The brain receives information about adiposity levels through circulating factors, such as insulin and leptin, and signals from the gastro-intestinal tract through vagal afferents and gut-derived hormones, such as ghrelin, cholecystokinin (CCK), peptide YY (PYY) and glucagon-like peptide-1 (GLP-1).…”
Section: Introductionmentioning
confidence: 99%